2013
DOI: 10.1080/09581596.2013.788787
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ positions in the breast screening debate, and media coverage of the debate: a qualitative study

Abstract: Against the backdrop of new research evidence suggesting breast screening causes avoidable harms and that women are not being given enough information to make informed decisions, we sought to explore the positions on breast screening adopted by a range of stakeholders, and coverage of this debate in the media. We sampled material from national newspapers, charity bodies' websites, and official bodies' websites over a two-year period, and analysed this using thematic content analysis.Charities' and official bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Similarly, Chen et al . () describe an emphasis on individual responsibilities for addressing cancer risk in media coverage of screening for breast cancer, noting that in the wake of debates surrounding the efficacy of breast cancer screening, its potential harms were less visible in the media than positive accounts from women or celebrities believing they had benefited from screening programmes.…”
Section: Cancer Risk and Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Chen et al . () describe an emphasis on individual responsibilities for addressing cancer risk in media coverage of screening for breast cancer, noting that in the wake of debates surrounding the efficacy of breast cancer screening, its potential harms were less visible in the media than positive accounts from women or celebrities believing they had benefited from screening programmes.…”
Section: Cancer Risk and Responsibilitymentioning
confidence: 99%
“…Musso and Wakefield's (2009) work also explores the portrayal of cancer risk in Canadian newspapers, and found that coverage most frequently emphasised the management of cancer risk through individual lifestyle change. Similarly, Chen et al (2014) describe an emphasis on individual responsibilities for addressing cancer risk in media coverage of screening for breast cancer, noting that in the wake of debates surrounding the efficacy of breast cancer screening, its potential harms were less visible in the media than positive accounts from women or celebrities believing they had benefited from screening programmes.…”
Section: Individualising Responsibility For Riskmentioning
confidence: 99%
“…Overdiagnosis is driven by a range of factors including: increasingly sensitive tests that identify indolent, nonprogressive, or regressive abnormalities; expanded disease definitions and lowered thresholds; creation of pseudo diseases; public enthusiasm for screening or testing and the desire for reassurance (Chen, Eborall et al 2014); clinicians' fear of missing a diagnosis or of litigation; and financial incentives (Moynihan, Henry et al 2014).…”
Section: Overdiagnosis and Overtreatment -The Potential Contribution Of Social Science Theorymentioning
confidence: 99%
“…Many likely contributing factors have been identified, including: increasingly sensitive tests that identify indolent, non-progressive or regressive abnormalities; expanded disease definitions and lowered thresholds for intervention; creation of ‘pseudo diseases’; public enthusiasm for screening or testing and the desire for reassurance15; clinicians’ fears of missing a diagnosis or of being held to account for decisions not to act16; and financial incentives 17. In an effort to develop a comprehensive overview, recent work from Australia has sought to map these possible drivers and link them to their potential solutions 18.…”
Section: Insights From Healthcare Improvement Researchmentioning
confidence: 99%